INTEGRATION OF DIGITAL TECHNOLOGY AND LOCAL WISDOM: THE ABCD APPROACH IN IMPLEMENTING SMART VILLAGE IN BUKIT TINGGI VILLAGE, BATU PUTIH, NORTH KOLAKA - Faiz, Ahmad; Raihan Fhadil Achmad, Muhammad; AlMushawwir; Yusril; Zuljalal Al Hamdany, Muhammad (International Journal of Multidisciplinary Reseach, 2025)
The Smart Village Community Service Program (KKN) aims to analyze the application of the Asset Based Community Development (ABCD) approach in supporting the transformation of Bukit Tinggi Village into a Smart Village based on local wisdom. Community service activities were carried out over 45 days through the stages of discovery, design, implementation, and reflection, with the active participation of the community, village officials, and local organizations. Data collection was conducted through observation, in-depth interviews, and documentation to identify the village's human, social, cultural, and economic resources. The results of the activities showed that the ABCD approach was effective in optimizing the role of the community in the village digitalization process, particularly through the development of a DIGIDES- based village website, management of official social media, preparation of public service infographics, and production of digital educational content. This program contributed to improving digital literacy, transparency of public services, and strengthening local identity amid the development of digital technology.